1985
DOI: 10.1287/mnsc.31.6.680
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Heuristics and Feedback in a Dynamic Decision Environment

Abstract: Research on cognitive processes in decision making has identified heuristics that often work well but sometimes lead to serious errors. This paper presents an investigation of the performance of heuristics in a complex dynamic setting, characterized by repeated decisions with feedback. There are three components: (1) A simulated task resembling medical decision problems (diagnosis and treatment) is described. (2) Computer models of decision strategies are developed. These include models based on cognitive heur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 49 publications
1
81
0
Order By: Relevance
“…Furthermore, learning in dynamic systems is often slow and weak, even with repeated trials, unlimited time, and performance incentives (Diehl & Sterman, 1995;Kleinmuntz & Schkade, 1993;Sterman, 1989aSterman, , 1989b. Many of these studies involved tasks of great complexity, and poor performance was often ascribed to the large number of entities and interactions, feedback delays, and information overload (Brehmer, 1990(Brehmer, , 1995Gonzalez, 2005a;Kleinmuntz, 1985;Omodei & Wearing, 1995).…”
Section: A Simple Stock and Flow Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, learning in dynamic systems is often slow and weak, even with repeated trials, unlimited time, and performance incentives (Diehl & Sterman, 1995;Kleinmuntz & Schkade, 1993;Sterman, 1989aSterman, , 1989b. Many of these studies involved tasks of great complexity, and poor performance was often ascribed to the large number of entities and interactions, feedback delays, and information overload (Brehmer, 1990(Brehmer, , 1995Gonzalez, 2005a;Kleinmuntz, 1985;Omodei & Wearing, 1995).…”
Section: A Simple Stock and Flow Problemmentioning
confidence: 99%
“…Furthermore, learning in dynamic systems is often slow and weak, even with repeated trials, unlimited time, and performance incentives (Diehl & Sterman, 1995;Kleinmuntz & Schkade, 1993;Sterman, 1989aSterman, , 1989b. Many of these studies involved tasks of great complexity, and poor performance was often ascribed to the large number of entities and interactions, feedback delays, and information overload (Brehmer, 1990(Brehmer, , 1995Gonzalez, 2005a;Kleinmuntz, 1985;Omodei & Wearing, 1995).More recent work, however, has shown that people make persistent mistakes even in the simplest dynamic systems, including systems consisting of one stock, one inflow, and one outflow, with no feedback processes, time delays, or nonlinearities (e.g., Booth Sweeney & Sterman, 2000;Cronin & Gonzalez, 2007;Sterman & Booth Sweeney, 2007). To illustrate, the ''department store" task (Sterman, 2002) presents participants with a graph showing the number of people entering and leaving a department store each minute over a 30-min interval (Fig.…”
mentioning
confidence: 99%
“…Experiments in both economics and psychology have focussed (with significant exceptions, e.g. Hogarth and Makridakis 1981, Kleinmuntz 1985, Brehmer 1986, Smith 1986) on static and discrete judgments.…”
Section: D-3876-1mentioning
confidence: 99%
“…Experiments in both economics and psychology have focussed (with significant exceptions, e.g. Hogarth and Makridakis 1981, Kleinmuntz 1985, Brehmer 1986, Smith 1986) on static and discrete judgments.Hogarth (1981, 198) emphasizes ...the continuous, adaptive nature of the judgmental processes used to cope with a complex, changing environment... With few exceptions...judgment researchers have focussed on discrete incidents (particular actions, predictions, and choices) that punctuate these continuous processes; furthermore, task environments are typically conceptualized to be stable.... [l]nsufficient attention has been paid' to the effect of feedback between organism and environment.The complexity and scale of corporate and economic systems renders experiments on the systems itself infeasible. This paper argues that experimental studies of the "feedback between organism and environment" in aggregate dynamic systems such as the economy can be conducted in the laboratory with computer simulation models.…”
mentioning
confidence: 99%
“…Case vignettes have been used to assess decision making across a range of clinical and professional settings, including welfare programs (Hagen 8c Owens-Manley, The decisions made by welfare-to-work staff can be seen as dynamic decisions (Kleinmuntz, 1985) in which a series of related decisions and actions inform each other over a period of time. Carroll and Johnson (1990) Table 1).…”
Section: Methodsmentioning
confidence: 99%